Influence of a newly-developed triathlon suit on the passive drag and body position - Ishikura, K.; Yoshimi, J.; Matsuda, A.; Yamashita, K.; Katsu, M.; Otsuka, S.; Tkakagi, H. (Procedia Engineering, 2014)
A new model triathlon suit (NMS) was developed to help the swimming performance of athletes. The NMS is made of highly compressed and highly water-repellent fabric, which is used in competitive swimwear. The aim of this study was to evaluate the NMS by measuring the passive drag and body position during underwater streamline position. The NMS and the old model suit (OMS) were worn by 11 highly competitive varsity swimmers (eight males and three females). The passive drag and body position were measured when both suits were worn in the circulating water channel. The coefficient of passive drag was calculated by the equation. On average, for the whole measurements, there was a reduction in passive drag when wearing the NMS suit of 1.1±5.3% compared with the OMS, whereas there was no statistically significant. The coefficient of the passive drag was not significant difference between both suits. Wearing the NMS showed higher body position compared to the OMS at any velocity, although not significantly. These results suggest that wearing the NMS might help improve swimming performance.